2006
DOI: 10.4049/jimmunol.176.12.7346
|View full text |Cite
|
Sign up to set email alerts
|

TCR-Dependent Cell Response Is Modulated by the Timing of CD43 Engagement

Abstract: Binding of Ag by the Ag receptor in combination with other stimuli provided by costimulatory receptors triggers the expansion and differentiation of T lymphocytes. However, it is unclear whether the time when costimulatory molecules interact with their counterreceptors with regards to Ag recognition leads to different T cell responses. Provided that the coreceptor molecule CD43 is a very abundant molecule evenly distributed on the membrane of T cell surface protruding 45 nm from the cell, we hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 54 publications
4
29
1
Order By: Relevance
“…It remains to be determined how the presence or absence of CD43 on T cells is regulating Th cell differentiation. Studies in human T cells have shown that CD43 costimulation in the presence and absence of TCR stimulation can induce IFN-␥ production and promote Th1 differentiation (42)(43)(44)(45). However, these findings have not been replicated in murine systems, making it unclear whether this plays a role in our model.…”
Section: -Immunized Cd43mentioning
confidence: 92%
“…It remains to be determined how the presence or absence of CD43 on T cells is regulating Th cell differentiation. Studies in human T cells have shown that CD43 costimulation in the presence and absence of TCR stimulation can induce IFN-␥ production and promote Th1 differentiation (42)(43)(44)(45). However, these findings have not been replicated in murine systems, making it unclear whether this plays a role in our model.…”
Section: -Immunized Cd43mentioning
confidence: 92%
“…This enhancement was significantly greater (p < 0.02) than that observed after the coligation of CD43 (2.3 ± 0.3-fold over OKT3 alone, mean ± SEM, n = 5 experiments, p < 0.001; Figure 2E). Because CD43 has been shown to transmit either costimulatory or inhibitory signals in certain model systems, we also measured the NF-AT:AP-1 responses of T cells stimulated in the presence of both anti-CD43 and VCAM-1 ( Figure 2D) (Fierro et al, 2006;Tong et al, 2004). Under our assay Immunity VLA-4 Inhibits Microcluster Translocation conditions, CD43 exhibited no inhibitory effect.…”
Section: Enhanced Adhesion Promotes Microcluster Formation But Is Insmentioning
confidence: 98%
“…Cells were stimulated with anti-CD3 (OKT3, 100 ng/ml; American Type Culture Collection, Manassas, VA) and anti-CD28 (500 ng/ml; Ancell Corp., Bayport, MN) mAbs at room temperature for 15 min, after which a secondary anti-mouse polyclonal antibody (rabbit anti-mouse immuImmunosuppressive Peptide Toxin from Scorpion Venom 373 at ASPET Journals on May 7, 2018 molpharm.aspetjournals.org noglobulin, 1 g/ml) was added to cross-link the primary antibodies (Fierro et al, 2006). Cells were then incubated at 37°C in 5% CO 2 for the indicated times.…”
Section: Methodsmentioning
confidence: 99%